Pore morphology of bijel-templated materials promotes migration and downregulates αSMA expression in human fibroblasts - Gonthier, Alyse R.; Botvinick, Elliot L.; Mohraz, Ali (Frontiers in Bioengineering and Biotechnology, 2025)
The efficacy of an implanted biomaterial is dependent on its ability to mitigate the foreign body response (FBR). Consequently, advancements in biomaterials design often focus on their immunomodulatory capability. Porous scaffolds have proven especially useful due to their capacity for cell infiltration and biomimicry of native tissues. Specifically, substrates with distinct microstructures have been shown to reduce fibrotic production and increase vascularization in vivo. Investigation of the direct relationship between FBR-implicated cell behavior and these materials, known as bicontinuous interfacially jammed emulsion gels (bijel)-templated materials (BTMs), has not yet been performed experimentally. In this study, we examine the influence of BTMs on the characteristics of human fibroblasts and assess the validity of existing computational results. The BTM, with its uniform pore size and negative Gaussian surface curvatures, is compared to the particle-templated material (PTM), which has constricting pore networks and variable surface curvature. Fibroblasts seeded into BTMs had less circular shapes, larger areas, increased motility, and reduced inflammation compared to cells seeded into PTMs. The specific behavior of cells within the PTM suggests that the reduction in migratory capability results from high local surface curvature. This corroborates previous computational work which predicted similar differences in cell shape and migration, as well as the influence of local curvature. These new experimental results provide key insights into the interaction between fibroblasts and biomaterial microstructure, prompting further investigation into the mechanisms behind these relationships.